2021
DOI: 10.1111/scd.12681
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations of congenital Zika virus infection in children with microcephaly: 18‐month follow‐up case series

Abstract: To describe oral manifestations in children born with microcephaly attributed to congenital Zika virus syndrome (CZS). Methods: Data was collected in semiannual intervals from 2017 to 2019, by oral exams of the children and interview with caregivers at a Public Dental Center in Rio de Janeiro, Brazil. A single calibrated examiner performed clinical examinations. Results:Of 38 eligible children, 34 were followed-up from 12 to 30 months of age, 20 boys and 14 girls. The mean age of emergence of their first prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 26 publications
(98 reference statements)
2
15
0
Order By: Relevance
“…In this study, one of the children had a severe delay in the eruption of the first deciduous tooth, occurring only in the 17th month of life. Overall, the pattern of delay is consistent with previous studies [7][8][9][10]24,[32][33][34]. In cases 2 and 5, alteration in the sequence of eruption of deciduous teeth was observed, as the maxillary central incisors were the first teeth to erupt; in addition, the event occurred beyond the expected time, at 13 and 15 months, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, one of the children had a severe delay in the eruption of the first deciduous tooth, occurring only in the 17th month of life. Overall, the pattern of delay is consistent with previous studies [7][8][9][10]24,[32][33][34]. In cases 2 and 5, alteration in the sequence of eruption of deciduous teeth was observed, as the maxillary central incisors were the first teeth to erupt; in addition, the event occurred beyond the expected time, at 13 and 15 months, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Delays in the chronology of eruption of deciduous teeth, alterations in the emergence sequence in the oral cavity [7][8][9], and the occurrence of disturbances in the development of the dental organ in number, shape, and structure indicate a possible role of ZIKV in odontogenesis [8]. Defects in dental enamel development, such as demarcated opacities and hypoplasia, have been reported in the deciduous dentition of children with CZS, evaluated for a period of 18 [9] to 36 months [8]. The distribution of occurrences was more frequent in the anterior teeth of the upper and lower arches, as well as in the posterior teeth located in the mandibular dental arch [8].…”
Section: Introductionmentioning
confidence: 99%
“…The studies involved a total of 795 children (178 were normotypic control children) ranging in age from 0 to 59 months. Seven studies reported data related to prematurity 10,12,14,18,19,31,32 and four related to birth weight 10,14,19,32 …”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported the criteria used for the diagnosis of microcephaly, 10,13–16,18,19–22,31–34 10 studies performed or had access to the result of the test used to detect ZIKV 10,16–20,22,31,33,34 and, 12 studies diagnosed the CZS by combining clinical, radiographic, and serological findings 10,15–20,22,31–34 (Appendix 3). Seven studies were funded by a government or university grant, 10,12,15,16,19,20,34 and 13 declared no conflicts of interest 10,13,14,17,18,20,21,31–35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation